Multi-Sensorimotor Training Improves Proprioception and Balance in Subacute Stroke Patients: A Randomized Controlled Pilot Trial - Lim, Chaegil (Frontiers in Neurology, 2019)
Introduction: To determine whether an advanced rehabilitation therapy combined with conventional rehabilitation therapy consisting of sensorimotor exercises that would be superior to a usual treadmill training in proprioception variation and balance ability of subacute stroke patients. Methods: Thirty subjects(post stroke duration : 3.96 ± 1.19 months) randomly assigned to either multi-sensorimotor training group (n=19) or treadmill training group (n=18). Both groups first performed conventional physical therapy for 30 min, after which the multi-sensorimotor training group performed multi-sensorimotor training for 30 min, and the treadmill training group performed treadmill gait training for 30 min. Both groups performed the therapeutic interventions 5 days per week for 8 weeks. The primary outcome(Proprioception variation) was evaluated using an acryl panel and electrogoniometer. The secondary outcome(Balance ability) was measured using the Biodex Balance system before intervention and after 8 weeks. Results: The multi-sensorimotor training and treadmill training groups showed a significant improvement in proprioception variation and balance(overall, A-P and M-L)(all P < 0.05). In particular, the multi-sensorimotor training group showed more significant differences in proprioception variation(P = 0.002) and anterior-posterior (A-P) balance ability(P = 0.033) than the treadmill training group. Conclusions: The multi-sensorimotor training program performed on multiple types of sensory input had beneficial effect on proprioception sense in the paretic lower limb and A-P balance. A large-scale randomized controlled study is needed to prove the effect of this training.